Microwaves initiated synthesis of activated carbon-based composite hydrogel for simultaneous removal of copper(II) ions and direct red 80 dye: A multi-component adsorption system - Oladipo, Akeem Adeyemi; Gazi, Mustafa (Elsevier, 2015)
We present a novel microwave initiated preparation of polyacrylamide/activated carbon hydrogel (PAAm-FAc) in this article and characterized by FT-IR, pHzpc and Boehm titration. The adsorbent was assessed for competitive adsorption of copper(II) and direct red 80 from a binary mixture in a single-staged batch process as a function of volume of binary mixture/mass of adsorbent (V0/M0) ratio at varying orders of second pollutant concentration. A competitive, multi-component Langmuir isotherm was used to express the adsorption process and the model was applied for calculating adsorbed or equilibrium individual pollutant concentration (Cad,eq,i or Ceq,i) at a fixed V0/M0 ratio for a combination of pollutants in a batch reactor. The data obtained indicated that the decrease of V0/M0 ratio with the addition of second pollutant influenced the amount of copper or direct red 80 removed. The prepared adsorbent is efficient and useful in multi-component adsorption system.
Due to copyright restrictions, the access to the publisher version (published version) of this article is only available via subscription. You may click URI and have access to the Publisher Version of this article through the publisher web site or online databases, if your Library or institution has subscription to the related journal or publication.
Keywords: Ferula communis; Copper; Competitive adsorption; Direct red 80; Microwave radiation